Pengembangan Media Pembelajaran Berbasis Multimedia Video Pada Siswa - Supriyaddin Supriyaddin; Andi Prayudi; Siti Mardiati (Inventor: Jurnal Inovasi dan Tren Pendidikan Teknologi Informasi, 2023)
The purpose of this study is to develop multimedia video-based learning media in network service technology subjects that are valid, practical and effective in class X Multimedia 2 SMK Negeri 1 Dompu. The type of research chosen by the researcher is the ADDIE model of research and development (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques are by means of interviews, observations, validation sheets, and questionnaires. The results of the learning media assessment by media experts are said to be "Very Valid" because the percentage of the acquisition score is 93%, while the assessment of learning media by media experts is said to be "Valid" with the percentage acquisition score of 67%, it can be concluded that the overall validation results of multimedia video learning media from both expert is 80% in the "valid" category, which means that the video-based learning media developed is in the feasible category in terms of material and media. Then the data from the questionnaire results from student responses consisting of the distribution of 10 answers with a score of five (5) is 88, a score of 4 is 81, an acquisition score is 324, and a score of three (3) is 31 with a score of 93, a numerical score Then two (2) which is 0 and the score number one (1) which is 0. processed using the practicality percentage formula which is 86%. So the product produced in the form of video-based learning media can be said to be practical and has gone through the calculation process in the table and then obtained the highest average percentage from the posttest which is equal to 86%. While the results of the analysis obtained from the pretest percentage, namely obtaining a proportion value of 73%. So the product produced in the form of video-based learning media can be said to be practical to use as a learning medium. Abstrak Tujuan penelitian ini yaitu mengembangkan media pembelajaran berbasis multimedia video pada mata pelajaran teknologi layanan jaringan yang valid, praktis dan efektif pada siswa kelas X Multimedia 2 SMK Negeri 1 Dompu. Adapun jenis penelitian yang dipilih oleh peneliti adalah jenis penelitian pengembangan (research and Development) model ADDIE (Analysis, Design, Development, Implementation, dan Evaluation). Teknik pengumpulan data adalah dengan cara wawancara, observasi, lembar validasi, dan angket. Hasil penilaian media pembelajaran oleh ahli materi dikatakan “Sangat Valid” dikarenakan presentase skor perolehan yaitu 93%, sementara penilaian media pembelajaran oleh ahli media dikatakan “Valid” dengan presentase skor perolehan 67%, dapat disimpulkan secara keseluruhan hasil validasi media pembelajaran multimedia video dari kedua ahli adalah 80% dengan kategori “valid” yang berarti media pembelajaran berbasis video yang dikembangkan masuk katagori layak dari segi materi dan media. Kemudian data hasil angket dari respon siswa yang terdiri dari distribusi jawaban sebanyak 10 dengan pemberian skor senilai lima (5) sebanyak 88, skor nilai 4 sebanyak 81, skor perolehan 324, dan skor nilai tiga (3) sebanyak 31 dengan skor 93, skor angka dua (2) yaitu 0 dan skor angka satu (1) yaitu 0. Lalu diolah dengan menggunakan rumus presentase kepraktisan yaitu 86 %. Jadi produk yang dihasilkan berupa media pembelajaran berbasis video tersebut dapat dikatakan praktis dan telah melalui proses perhitungan pada tabel lalu diperoleh presentase rata-rata tertinggi dari postest yaitu sebesar 86%. Sementara hasil analisis yang diperoleh dari presentase pretest yaitu memperoleh nilai persentase 73%. Jadi produk yang dihasilkan berupa media pembelajaran berbasis video tersebut dapat dikatakan praktis untuk digunakan sebagai media pembelajaran.